A Virtual Reality System for Treatment of Phantom Limb Pain using Game Training and Motion Tracking - Henriksen, Bartal; Nielsen, Ronni; Szabo, Laszlo; Evers, Nicolaj; Kraus, Martin; Geng, Bo (International Journal of Virtual Reality, 2016)
This paper describes the implementation of a phantom limb pain (PLP) home-based system using virtual reality (VR) and a motion sensor to immerse the users in a virtual environment (VE). The work is inspired by mirror therapy (MT), which has been used to relieve PLP. The target patient group focuses on unilateral upper-limb amputees with phantom pain. Using a motion sensor, the system tracks the movement of a user's hand and translates it onto the virtual hand. The system consists of exercises including opening and closing the hand, rotating the hand, and finer finger movements. These exercises are conveyed in the VR as three games: (1) A bending game, where the patients have to bend a rod, (2) a box game where the patients pick up and place boxes with their hands, (3) and a button memory game where the patients have to push buttons in a given sequence. These games were tested on twelve healthy participants to evaluate if the games encouraged similar movements as in MT. Prior to the experiment a preliminary test was conducted on an amputee with PLP to gather qualitative feedback from an end-user. The results indicated that the games did convey the exercises from the MT, although further testing is needed.